Problems Of Skin Cover In Injuries Of Lower Limb With Tissue Loss - A. Ganguli (Indian Journal of Plastic Surgery)
Twenty seven cases of different types of injuries of the lower limb with skin loss treated by various means have been reviewed. The various methods of treatment have been evaluated and the methods giving the best result have been stressed.